Metadata: A pedagogical tool for the teaching of map projections in Elementary School - Georgia Intzidou; Nikos Lambrinos; Christos Tourtouras; Fani Seroglou (European Journal of Geography)
Digital interactive maps include a set of metadata, which show the purpose the user can use the map. Metadata in digital interactive world maps inform users about important information, such as the map projection. This research examines whether the educational and teaching use of the metadata of digital interactive maps construct a tool in the approach to the issue of map projection in Elementary School. The research was carried out in 17 Elementary Schools of Thessaloniki, Greece, where 6th-grade students (? = 655) were engaged in a series of activities related to metadata and map projections. ArcGIS Online was used as a didactic tool. Results showed that metadata of digital interactive maps have a great pedagogical value. The identification of the different information in the metadata, i.e., the map projection, and the students’ decision of what they can and cannot study with each map, is an important finding regarding their educational relevance.